Family resilience and psychological well‐being among Chinese breast cancer survivors and their caregivers - Li, Yuli; Qiao, Yuanjing; Luan, Xiaorong; Li, Shaojie; Wang, Kefang (European journal of cancer care, 2019)
Walsh's family resilience theory indicated that families could foster resilient outcomes among their members when they are facing changes or crises. However, little is known about family resilience and psychological well‐being among Chinese breast cancer survivors and their caregivers. Therefore, this study aimed to examine the direct and indirect relationships between family resilience, breast cancer survivors' post‐traumatic growth (PTG), quality of life (QOL), and their principal caregivers' caregiver burden. A total of 108 breast cancer survivors/principal caregivers pairs completed a cross‐sectional questionnaire survey in a comprehensive cancer of a public hospital in Shandong Province, China. The structural equation modelling (SEM) results showed that family resilience had direct and indirect effects on QOL and caregiver burden, and it was positively related to the PTG of the survivors. The survivors' PTG was positively related to their QOL, and their QOL was negatively associated with caregiver burden. Therefore, a better understanding of how family resilience contributes to PTG and QOL of the survivors and caregiver burden could help clinicians tailor interventions to enhance interventions aimed at improving both survivors' and caregivers' well‐being.